Unlocking the keto code ebook The revolutionary new science of keto that offers more benefits without deprivation. - Gundry, MD, Steven R. (The Plant Paradox., 2022)
From the author of the New York Times bestselling Plant Paradox series comes this revolutionary take on the keto diet that debunks common myths and shows readers how to reap the rewards of keto with less restriction Like many doctors and nutrition experts, bestselling author Dr. Steven Gundry has long endorsed the ketogenic diet—a style of eating that heavily restricts carbohydrate intake to make the body burn fat for fuel. Because ketosis offers a variety of health benefits, including weight loss, reduced risk of illness, and enhanced energy, Dr. Gundry believed his patients' efforts to adhere to the challenging regimen was worthwhile. That is, until his research uncovered a shocking truth: We've gotten keto all wrong. In Unlocking the Keto Code, Dr. Gundry reveals the biological mechanism that makes keto diets so successful: a cellular process known as "mitochondrial uncoupling." As it turns out, ketones are not the magical fuel source they've been made out to be; in fact, the body cannot run on ketones and fats alone. Over the long term, a very low carb-diet can lead to muscle wasting and poor cognitive health. Luckily, you don't have to restrict all carbs to reap the benefits of ketosis; you simply have to have enough ketones and other plant compounds called polyphenols present in your body to "unlock" the process of mitochondrial uncoupling. In this insightful, empowering, eminently practical book. Dr. Gundry explains the many ways readers can ignite this process, from feasting on plant-based foods (carbs that are typically off-limits on a keto diet!) to enjoying ketone generating foods such as goat and sheep milk products, to implementing a timed eating schedule. You will even discover the real reason how superfoods, even apple cider vinegar, work their magic; and its not what they you think! Grounded in cutting-edge science, this is the book for all the people who have tried and failed on a keto diet; for vegetarians and vegans who want to go keto; and for anyone who wants to lose weight and enjoy better health while eating a wide variety of foods. With food lists, hacks, and all-new recipes, Unlocking the Keto Code makes going keto easy and enjoyable for the first time.